2022
DOI: 10.17977/um062v2i122020p613-619
|View full text |Cite
|
Sign up to set email alerts
|

Survei Daya Tahan VO2max Peserta Ekstrakurikuler Bolavoli di Sekolah Menengah Pertama (SMP)

Abstract: The research objective was to determine the VO2max endurance of volleyball extracurricular participants at SMP Negeri 21 Malang. This study used survey techniques with percentage descriptive analysis. The conclusion of this study is that the VO2max endurance level of volleyball extracurricular participants at SMP Negeri 21 Malang as a whole, both girls and boys are mostly in the very bad category with 73 percent each, so that means the VO2max endurance of volleyball extracurricular participants at SMP Negeri 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Based on these results, it can be concluded that the VO2max endurance of the women's volleyball athletes from the Brojomusti club is still partially lacking. Relevant research on volleyball extracurriculars shows a very poor category (Ihsanti & Haryoko, 2022) . Next, the VO2max level of wrestling extracurricular students is in the moderate category (Nesra Barus, 2020) .…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, it can be concluded that the VO2max endurance of the women's volleyball athletes from the Brojomusti club is still partially lacking. Relevant research on volleyball extracurriculars shows a very poor category (Ihsanti & Haryoko, 2022) . Next, the VO2max level of wrestling extracurricular students is in the moderate category (Nesra Barus, 2020) .…”
Section: Discussionmentioning
confidence: 99%
“…Sejalan dengan pernyataan bahwa kelelahan yang dirasakan seorang atlet bola voli dapat menyebabkan menurunnya konsentrasi yang mengakibatkan atlet tidak bisa berkonsentrasi dengan baik terhadap suatu pertandingan sehingga membuat performa atlet bola voli pun juga menurun (Ihsanti, 2020).…”
Section: Pendahuluanunclassified